Short window of opportunity for brown bear (Ursus arctos) predation on reindeer (Rangifer tarandus) calves - Kjellberg, Linnéa Eleonora (2014)
To improve and develop a management system for reindeer husbandry regarding minimizing depredation by brown bears, knowledge about current depredation patterns is required. Using data obtained from a predation study regarding brown bear predation on reindeer from 2010 to 2012 I aimed at investigating what solutions are available to minimize brown bear predation on reindeer calves. This study has shown that predation on reindeer calves by brown bears in relation to the dates of birth for the calves in the study area was delayed by approximately one week. It has also shown that bears stopped killing reindeer calves approximately one week after the last calf in the studied herds was born. Mobility of the reindeer calves is assumed to be a determining factor affecting hunting success, since encounters then decrease. The two most feasible ways to minimize predation by brown bears can be to; 1) ensure that there is an adequate proportion of male reindeer in the herds so that all female reindeer are mated during the first rutting period and; 2) to minimize human disturbances during sensitive periods such as the rutting and calving period.